2009
DOI: 10.2174/187221009788490068
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Nanoparticle Preparation by Spray and Microemulsion Methods

Abstract: Micro- and nano-sized metal, semiconductor, pharmaceutical, and simple or complex ceramic particles have numerous applications in the development of sensors, thermal barrier coatings, catalysts, pigments, drugs, etc. The challenges include controlling the particle size, size distribution, particle crystallinity, morphology and shape, being able to use the nanoparticles for a given purpose, and to produce them from a variety of precursors. There are several methods to produce nanoparticles, each suitable for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…Thermo-physical processes and surface dynamics like shape oscillation mechanisms in vaporizing functional droplets at different spatio-temporal scales are pivotal to a diverse range of practical applications such as pharmaceutical drug delivery, innovative fuel injection strategies in combustors/premixers, spray combustion, surface patterning in micro channels, solution precursor plasma spray technique (SPPS) for thermal barrier coating, and biological crystal growth. [1][2][3][4] Controlling droplet deformations through physics based understanding at different scales can revolutionize many application areas. Single droplet represents the sub-grid unit of the spray.…”
Section: Introductionmentioning
confidence: 99%
“…Thermo-physical processes and surface dynamics like shape oscillation mechanisms in vaporizing functional droplets at different spatio-temporal scales are pivotal to a diverse range of practical applications such as pharmaceutical drug delivery, innovative fuel injection strategies in combustors/premixers, spray combustion, surface patterning in micro channels, solution precursor plasma spray technique (SPPS) for thermal barrier coating, and biological crystal growth. [1][2][3][4] Controlling droplet deformations through physics based understanding at different scales can revolutionize many application areas. Single droplet represents the sub-grid unit of the spray.…”
Section: Introductionmentioning
confidence: 99%
“…Use of polymeric particulate delivery systems (micro-and nanoparticles) is one of the best potential delivery approaches that can both improve stability against degradation and enhance intestinal absorption. In our studies, we have found that the development of ZnPPencapsulated lipid nanoparticles, prepared by the controlled cation-induced micro-emulsion (46,48) and spray-drying methods (48)(49)(50)(51), seems to be the most promising. In particular, 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPSS) and distearoyl-sn-glycero-phosphocholine (DPSC) are biodegradable phospholipids approved by the FDA for use in premature infants as surfactants.…”
Section: Decision To Use Znppmentioning
confidence: 99%
“…The inverse (w/o) microemulsions approach is a promising method for the preparation of NPs owing to its simplicity, giving the controlled particle size and the highly homogenous product because of the effi cient mixing at the molecular level [19] . Crosslinking is a useful way to improve the physical chemical properties of polysaccharide.…”
Section: The Formation and Characterization Of Sa-pnpsmentioning
confidence: 99%